Effect of selenium on nutritive value of purslane (Portulaca oleracea L.) - Khedr F. Gamal; Hoda Mohamed Salama; Shimaa A. Ismaiel (European Journal of Biological Research, 2018)
Purslane (Portulaca oleracea) one of the auxiliary plants was traditionally consumed in many parts of the world for its nutritional and medicinal benefits. The nutrient components of purslane such as total protein, total carbohydrates and mineral content such as macro elements (Na, K, Ca and Mg) and micro elements (Fe, Cu, Pb and Zn) were estimated at different concentrations of selenium which treated in soil where the plant cultivated. The protein and carbohydrate contents of leaves as well as protein of stems increase with increasing the selenium concentration, while protein and carbohydrate of roots as well as carbohydrate of stems decrease with increasing Se concentration. The mineral content was also affected by Se concentration, Fe, Cu and Zn of leaves decreased with increasing Se concentration, while K, Ca, Mg and Na are directly proportional with Se concentration. In stems, Zn only is inversely proportional with Se concentration. In roots, Fe, Cu, Mg and K are inversely proportional with Se concentration, while Na, Ca and Zn are directly proportional. The findings of this study revealed that carbohydrates, protein and mineral contents of purslane can be affected and controlled by selenium concentration.